2022
DOI: 10.1007/jhep08(2022)054
|View full text |Cite
|
Sign up to set email alerts
|

Effective field theories and cosmological scattering equations

Abstract: We propose worldsheet formulae for wavefunction coefficients of the massive non-linear sigma model (NLSM), scalar Dirac-Born-Infeld (DBI), and special Galileon (sGal) theories in de Sitter momentum space in terms of the recently proposed cosmological scattering equations constructed from conformal generators in the future boundary. The four-point integrands are assembled from simple building blocks and we identify a double copy prescription mapping the NLSM wavefunction coefficient to the DBI and sGal wavefunc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 86 publications
1
9
0
Order By: Relevance
“…and used to explore the double copy for effective scalar theories in [50] (the double copy for effective scalar theories in AdS was also explored from various other points of view in [53,67,68]). In more detail, a generalised double copy for 4-point wavefunction coefficients was proposed in terms of unfixed parameters encoding masses and curvature corrections.…”
Section: Double Copymentioning
confidence: 99%
See 3 more Smart Citations
“…and used to explore the double copy for effective scalar theories in [50] (the double copy for effective scalar theories in AdS was also explored from various other points of view in [53,67,68]). In more detail, a generalised double copy for 4-point wavefunction coefficients was proposed in terms of unfixed parameters encoding masses and curvature corrections.…”
Section: Double Copymentioning
confidence: 99%
“…We will focus on effective scalar theories with mass m 2 = ∆(d − ∆). The discussion will be very schematic but the interested reader can find more details in [50]. A tree-level n-point wavefunction coefficient can be written as an integral over n-punctures on the sphere:…”
Section: Double Copymentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it would be interesting to investigate whether the double copy that has been identified for on-shell amplitudes also extends to off-shell aspects such as correlators and wavefunctionals. This issue was addressed very recently [28], where it was found that the most straightforward implementation of the double copy structure does not work (however, see also the analysis of [72] employing cosmological scattering equations). Given the offshell mapping outlined in section 2, it would be interesting to see whether this could be adapted for the gravity-coupled SO(M, N ) NL σ-model, and whether this would allow for a mapping onto multi-DBI and SG.…”
Section: Jhep10(2022)066mentioning
confidence: 99%